Ecomorphological, space, and mineral relations of dermal denticles in angular angel shark (Squatina guggenheim) - de Lima Viliod, Marcela Coffacci [UNESP]; Rangel, Bianca de Sousa; Rocha, Lara Caetano [UNESP]; dos Santos Domingos, Júlia Ferreira; Malavasi-Bruno, Carlos Eduardo; de Amorim, Alberto Ferreira; Watanabe, Ii-Sei; Ciena, Adriano Polican [UNESP] (Wiley, 2021)
Shark skin is predominantly specialized for swimming and protection, with the dermal denticle being the main structure associated with these abilities. The dermal denticle is a mineral structure with a unique morphology for each species, which allows its use as a taxonomic tool. Few studies have investigated the microscopy aspects of skin and dermal denticles, considering the high diversity of sharks. Here, we investigated the three-dimensional morphoquantitative aspects and mineral composition of dermal denticles in different regions of the angular angel shark, Squatina guggenheim, using scanning electron microscopy and dispersive energy system. With the microscopy, we were able to observe that the dermal denticle morphology changes according to the area it is located. It was possible to describe the dermal denticles individually, from root to the crown, highlighting all of their individualities. Through the dispersive energy system, we showed the proportions of each mineral found in the denticle, by area, demonstrating the composition and the particularities of crown, body, and root, where whitlockite was described for the first time in elasmobranchs. In this way, the present study presented the specificities of the dermal denticles of S. guggenheim, as well sought to understand the different structure functions for the animal, thus assisting future research in animal morphology.
Keywords: anatomy; elasmobranch; morphology; placoid scale; skin; structure